2020
DOI: 10.1038/s41598-019-56875-0
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cell Culture Density on the Cytotoxicity of Adipose-Derived Stem Cells Induced by L-Ascorbic Acid-2-Phosphate

Abstract: various concentrations of A2-P along with an antioxidant NAC (3 mM; Sigma) for 20 h. ASCs without NAC treatment were used as controls. The cell morphology was observed under a microscope, and alamar blue assay was employed to assess cell viability. Statistical analysis. All measurements are presented as means ± standard deviation. Statistical significance was evaluated using an independent-sample Student's t-test or ANOVA followed by the Tukey post-hoc test. When the Tukey test was used, each group was compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…In addition, we observed severe damages of neuronal cell body when subjected to 20–30 μM acrolein. The discrepancy of acrolein-induced neurotoxicity between LDH cytotoxicity assay and neurite outgrowth assay may be due to the cell density (5 × 10 6 cells in the LDH assay vs. 3 × 10 5 cells in the immunostaining study) since the lower density of seeding cells, the higher cytotoxicity is induced 27 , 28 . Moreover, our data showed that acrolein is capable of inducing HO-1, FDP-lysine and α-synuclein aggregation as well as apoptosis and necroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed severe damages of neuronal cell body when subjected to 20–30 μM acrolein. The discrepancy of acrolein-induced neurotoxicity between LDH cytotoxicity assay and neurite outgrowth assay may be due to the cell density (5 × 10 6 cells in the LDH assay vs. 3 × 10 5 cells in the immunostaining study) since the lower density of seeding cells, the higher cytotoxicity is induced 27 , 28 . Moreover, our data showed that acrolein is capable of inducing HO-1, FDP-lysine and α-synuclein aggregation as well as apoptosis and necroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…While in vitro systems do not have these features, they can recapitulate relevant aspects of in vivo models using specialized cell culture scaffolds and multiple human cell-types. Human cells can express cytokines and chemokines at a level concordant with humans if cell seeding density and cell-type ratios are purposefully applied and proper cell differentiation has occurred [60]. For this study, scanning electron microscopy proved to be useful in observing how cells interact with each other as well as qualifying individual cell-type differentiation and effects of seeding densities.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose-derived stem cells were isolated from the subcutaneous fat tissue of four non-smoking, non-diabetic female donors with an average age of 45 years (32-57 years) and an average body mass index of 24.6 (21.0-26.6) as described previously (Wu et al, 2020). The study protocol has been approved by the Research Ethics Committee of National Taiwan University Hospital, and the informed consent has been obtained from each donor of adipose tissue.…”
Section: Isolation and Culture Of Human Ascsmentioning
confidence: 99%